Applying Star Athletica’s Teachings in the Copyright Office - Kasunic, Robert (The Columbia Journal of Law & the Arts, 2020)
The Copyright Office does not have all the answers about where the lines are drawn between works of applied art and works of artistic craftsmanship. I don’t think the decision and opinion in Star Athletica answered all of the questions that we had. And in many ways it did not answer any of them, and in part made some of the issues more confusing. Because as Jane Ginsburg had said, the dress designs at issue were all filed with the Copyright Office as two-dimensional drawings. Some of them did depict the cheerleader outfit as well. But these were never being claimed as three- dimensional dress designs or anything else. The focus of these was on the applied art and not on the drawings of cheerleader uniforms. Going back for a minute to prior to the Star Athletica decision, the Copyright Office’s prior approach to separability was that the pictorial, graphic, or sculptural feature satisfies the conceptual separability requirement only if the artistic feature and the useful article could both exist side-by-side and be perceived as fully realized separate works; one an artistic work and the other as a useful article. And to us this worked very well for quite some time, to look and see whether there was something that was fully separable as an artistic work—such as a pictorial work or sculptural features that would be separable—but still leaving the useful article intact.